The Role of Bawaslu in Preventing Money Politics in the 2019 Legislative Election in Gorontalo City - Pakaya, Awang Dharmawan ramadhan; Makkulawuzar, Kindom; Rusmulyadi, Rusmulyadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
to ensure that the holding of general elections is not polluted by disgraceful acts, so that in addition to upholding the rule of law and raising the dignity of society from the habit of committing acts of money politics towards holding honest and fair general elections. The aim of the research is to determine the role of Bawaslu in preventing money politics in the 2019 legislative elections in Gorontalo City. This research uses normative legal research (normative law study) using normative case studies in the form of legal behavior products. The main point of study is law which is conceptualized as a norm or rule that is merely in society and becomes a reference for everyone's behavior. Bawaslu's role in the 2019 regional elections was carried out in accordance with Law No. 15 of 2011 concerning the Implementation of General Elections. Similar to what has been proven by the money politics violations that occurred in Gorontalo City in 2019, there were acts of promising and/or giving money or other materials to influence the holding of elections and/or elections in a structured, systematic and massive manner. Awareness about money politics must be based on shared awareness. Public Knowledge about Politics, of course, candidate pairs and the public must be able to change thought patterns that have an impact on social culture. Both candidate pairs and society must change their perspective. Not only giving, but also changing thought patterns which will later have a permissive impact.